Tourist Visit Decisions: Testing the Role of Social Media Marketing, Tourist Attraction and Destination Image on Urban Tourism in Malang City - Fadilla, Dian; Winarno, Agung; Dhewi, Titis Shinta (Technium Business and Management, 2025)
The rapid growth of tourism today must be supported by adequate technological literacy, especially the management and management. The purpose of this research is to explore and test the role of tourist attraction and destination image in mediating the influence of social media marketing on tourist visit decisions to urban tourist destinations. The research approach is quantitative causal comparative or ex-post facto. The research location is an urban tourist destination which includes Glintung water street, Kampoeng Heritage Kajoetangan and Kampung Sanan Tempe. The thematic village is included in the edu-tourism village which has its characteristics, also not only as a vacation spot but provides education to visitors so that it becomes an added value as a tour. Data collection was carried out by distributing closed questionnaires and interviews. Data analysis used Structural Equation Modeling (SEM) techniques to test the relationship between variables. The results showed that Social Media Marketing has a positive and significant effect on Tourist Attraction, Destination Image, and Tourist Visit Decisions. In addition, Tourist Attraction and Destination Image are also proven to have a direct effect on Tourist Visit Decisions. Social Media Marketing also has an indirect effect on visit decisions through the mediating role of Tourist Attraction and Destination Image. This shows that social media is not only effective as a promotional medium, but also plays a strategic role in shaping destination image and perception of tourist attraction. The implications of this study show the importance of relevant, creative, and digitally appropriate content strategies in tourism marketing. Tourism village managers are expected to continue optimizing the use of social media as a powerful communication tool to increase tourist visits and strengthen the sustainability of the edu-tourism village.